Multiple positive solutions to a p-Kirchhoff equation with logarithmic terms and concave terms - Liang Jin-Ping; Wang Ran-Ran; Wang Yue (Open Mathematics)
In this article, we focus on a class of pp-Kirchhoff-type equations that include logarithmic and concave terms. By applying the variational method, we establish the existence and multiplicity of positive solutions.